2014
DOI: 10.1681/asn.2013080883
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking to the Apical and Basolateral Membranes in Polarized Epithelial Cells

Abstract: Renal epithelial cells must maintain distinct protein compositions in their apical and basolateral membranes in order to perform their transport functions. The creation of these polarized protein distributions depends on sorting signals that designate the trafficking route and site of ultimate functional residence for each protein. Segregation of newly synthesized apical and basolateral proteins into distinct carrier vesicles can occur at the trans-Golgi network, recycling endosomes, or a growing assortment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 166 publications
3
86
1
1
Order By: Relevance
“…It has been suggested that, in inherited PKD, the translocation of transporters from the basal to the apical membrane may participate to cysts enlargement through an increase of fluid secretion [7,26]. In the present study, we failed to detect any change of the apico-basal polarity in cells lining tubular dilations.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…It has been suggested that, in inherited PKD, the translocation of transporters from the basal to the apical membrane may participate to cysts enlargement through an increase of fluid secretion [7,26]. In the present study, we failed to detect any change of the apico-basal polarity in cells lining tubular dilations.…”
Section: Discussioncontrasting
confidence: 83%
“…PKHD1 encodes for fibrocystin, a large transmembrane protein whose function is still unknown [5]. Despite differences in the age of onset, the severity of the disease or the localization of the cysts, it has been suggested that common mechanisms are involved in cyst formation, including cell proliferation and apoptosis [6], disturbance of cell polarity and cell-matrix interaction [7], enhanced fluid secretion, or loss of oriented cell division [8]. On the other hand, the primary cilium as well as calcium signaling have been suggested to play a role [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Such cell-line-specific differences in protein trafficking proteomes may explain classical differences in polarized expression among independent clones of the same cell type [41]. Similar differences in SLC4A1 dRTA mutant polypeptide targeting were recently observed in polarized cell lines and in mice.…”
Section: Discussionmentioning
confidence: 69%
“…At least in epithelial cells, sorting along the secretory pathway is not limited to the dichotomous allocation of proteins into shared carriers bound for the apical or the basolateral surface. It appears that in many and perhaps in most cases, proteins bound for delivery to the same subdomain of the plasma membrane are transported by distinct cadres of carrier vesicles that pursue different itineraries and that manifest specific biochemical properties (Farr et al , 2009, 2015; Stoops and Caplan, 2014; Stoops et al , 2015). The growing number and variety of these pathways suggests the intriguing possibility that each newly synthesized protein may follow its own customized variation on the secretory pathway and be packaged into vesicles that carry no other cargoes.…”
Section: The Next 50 Years: How Does the Secretory Pathway Work And Wmentioning
confidence: 99%